2017
DOI: 10.1530/joe-17-0190
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of exercise training in adipose tissue do not require FGF21

Abstract: Exercise enhances insulin sensitivity; it also improves adipocyte metabolism and reduces adipose tissue inflammation through poorly-defined mechanisms. Fibroblast growth factor 21 (FGF21) is a pleiotropic hormone-like protein whose insulin-sensitizing properties are predominantly mediated via receptor signaling in adipose tissue (AT). Recently, FGF21 has also been demonstrated to have anti-inflammatory properties. Meanwhile, an association between exercise and increased circulating FGF21 levels has been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…MR significantly reduced expression of Ccl2 , Itgam , and Itgax in liver and Ccl2 , Adgre1 , Itgam , and Itgax in adipose tissue of Fgf21 ‐/‐ mice (Figure ). These findings are in line with a previous study that reported that although exercise both increased FGF21 and reduced inflammation, FGF21 was not required for the exercise‐induced reduction in inflammation in adipose tissue . As previously reported , MR produced an unexpected reduction in food intake in the Fgf21 ‐/‐ mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…MR significantly reduced expression of Ccl2 , Itgam , and Itgax in liver and Ccl2 , Adgre1 , Itgam , and Itgax in adipose tissue of Fgf21 ‐/‐ mice (Figure ). These findings are in line with a previous study that reported that although exercise both increased FGF21 and reduced inflammation, FGF21 was not required for the exercise‐induced reduction in inflammation in adipose tissue . As previously reported , MR produced an unexpected reduction in food intake in the Fgf21 ‐/‐ mice.…”
Section: Discussionsupporting
confidence: 93%
“…The greater expression of these genes indicates that Fgf21 ‐/‐ mice are not only more susceptible to HFD‐induced inflammation but are also likely at greater risk for insulin resistance. Indeed, Fgf21 ‐/‐ mice were shown to have greater adipose tissue inflammation and insulin resistance compared with WT mice . Similarly, others showed that Fgf21 ‐/‐ mice had elevated levels of inflammation in pancreas when fed a HFD compared with WT mice .…”
Section: Discussionmentioning
confidence: 98%
“…One possible reason is that the higher levels of circulating FGF21 in pregnant women with GDM could be a compensatory response to the underlying differences in maternal physiology such as higher insulin resistance at the start of the pregnancy, poor reserve in insulin secretion capacity, and low-level inflammation in GDM subjects [27][28][29]. Additionally, circulating FGF21 levels are associated with overeating [30]; hence, increased food intake during pregnancy might also contribute to higher FGF21 levels in GDM subjects. Besides, increased FGF21 levels could reduce the appetite for sugar and preference for carbohydrate, and promote protein ingestion [31,32], thereby ensuring the supply of sufficient essential nutrients during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, voluntary wheel running reduced adiposity, adipose tissue inflammation, hyperinsulinemia, and hepatic fatty acid content and oxidation in both FGF21 KO mice and their control littermates (44,129). On the contrary, in mice fed with a high fat diet (HFD), voluntary wheel running did not improve hepatic triglyceride content and glucose tolerance but prevented weight and fat mass gain independently of genotype (97).…”
Section: Moreover In Cultured Skeletal Muscle Cells Fgf21 Expressiomentioning
confidence: 98%